Antonio Machado and the Apocryphal Tradition - Brioso, Jorge (Anales del Seminario de Historia de la Filosofía, 2007)
In this study I focus on the importance of the concept of the apocryphal to understand the work of Antonio Machado in its entirety. The concept of the apocryphal implies a critical position before tradition: the negation-forgetting of the real past, the affirmation reinvention of a possible past. The apocryphal comes to solve, according to Machado, the great crises that modern poetry faced: the loss of the ties that bound humankind and the universe, the relationship between high culture and mass culture, the relationship between the ethical and the aesthetic in the work of art.